Feyerabend on politics, education, and scientific culture. (June 2016) - Kidd, Ian James
Abstract: The purpose of this paper is to offer a sympathetic reconstruction of the political thought of Paul Feyerabend. Using a critical discussion of the idea of the 'free society' it is suggested that his political thought is best understood in terms of three thematic concerns— liberation, hegemony, and the authority of science—and that the political significance of those claims become clear when they are considered in the context of his educational views. It emerges that Feyerabend is best understood as calling for the grounding of cognitive and cultural authorities—like the sciences—in informed deliberation, rather than the uncritical embrace of prevailing convictions. It therefore emerges that a free society is best understood as one of epistemically responsible citizenship rather than epistemically anarchistic relativism of the 'anything goes' sort—a striking anticipation of current debates about philosophy of science in society. Highlights: I offer a sympathetic reconstruction of the political thought of Paul Feyerabend. The idea of the 'free society' is untenable, but reflects a set of sensible concerns. Feyerabend called the grounding of the authority of science in informed deliberation, rather than the uncritical embrace of prevailing convictions.